Fatal occupational injuries among U.S. law enforcement officers: A comparison of national surveillance systems1. Issue 6 (26th March 2013) - Tiesman, Hope M.; Swedler, David I.; Konda, Srinivas; Pollack, Keshia M.
Abstract Background This study describes and compares the three surveillance systems used to record occupational injury fatalities among U.S. law enforcement officers (LEOs). Methods The Census of Fatal Occupational Injuries (CFOI), National Law Enforcement Officer Memorial Fund database (NLEOMF), and Law Enforcement Officers Killed and Assaulted reports (LEOKA) were examined for LEO deaths between 2003 and 2009. Fatality rates per 100, 000 workers were calculated and compared. Results Between 2003 and 2009, the NLEOMF reported 1, 050 fatalities (rate of 16.4 per 100, 000 workers), the CFOI reported 968 fatalities (15.1 per 100, 000), and the LEOKA recorded 853 fatalities (13.3 per 100, 000). The LEOKA under‐counted the number of fatalities compared to the NLEOMF and CFOI. Discrepancies were found between the LEOKA, NLEOMF, and CFOI regarding age, race, and Hispanic origin. Similar patterns for cause of fatality were found; however, the NLEOMF recorded a higher number of "other" fatalities compared to the other two systems. Conclusions This study fills a critical knowledge gap by providing an overview of the three surveillance systems used to enumerate LEO occupational deaths. Understanding the differences across the systems is critical when utilizing them for surveillance research. Am. J. Ind. Med. 56:693–700, 2013. © 2013 Wiley Periodicals, Inc.